2017
DOI: 10.2298/jas1703241m
|View full text |Cite
|
Sign up to set email alerts
|

Productivity of apricot cultivars of medium late and late maturity in the Belgrade area

Abstract: Characteristics of productivity and growth (yield per tree, trunk crosssectional area, yield efficiency and fruit weight) were studied in 30 apricot cultivars of medium late and late maturity in the Belgrade area during the six-year period (2009?2014). The cultivar ?Hungarian Best? was used as a control for comparison. The period of study was divided into initial bearing (trees aged three to four years) and full bearing (trees aged five to eight years). Significant differences in yield betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Fruit yield is one of the most important parameters for selection of cultivars and objectives of apricot breeding[Rezaei et al 2020, Shamsolshoara et al 2021. Although the Shahroudi cultivar along with four other genotypes had the highest tree yield, but its value is lower than that ofEbadi et al [2020] (38.3 kg/tree), which is due to the trees not reaching the economic bearing ages Milatovic et al [2017]. found that the initial bearing of apricot cultivars has a direct relationship with their full bearing.…”
mentioning
confidence: 74%
“…Fruit yield is one of the most important parameters for selection of cultivars and objectives of apricot breeding[Rezaei et al 2020, Shamsolshoara et al 2021. Although the Shahroudi cultivar along with four other genotypes had the highest tree yield, but its value is lower than that ofEbadi et al [2020] (38.3 kg/tree), which is due to the trees not reaching the economic bearing ages Milatovic et al [2017]. found that the initial bearing of apricot cultivars has a direct relationship with their full bearing.…”
mentioning
confidence: 74%